Role of Entrepreneurship and Small Business in National Development - Karki, Bir Bahadur (Journal of Nepalese Business Studies, 2008)
Entrepreneurship and small business play vital role in national development for both types of countries i.e. developed and developing countries like Nepal. Without having entrepreneurship. Government is not able to develop country itself. Most of the Nepalese people do not have ideas and skills about entrepreneurship and entrepreneur. Although, they have been trying to establish as well as operate cottage and small businesses all over Nepal. Special focus has been given on Central and Eastern Development Region. Data shows that most of the Nepalese people are not economically active still now. Therefore, Government should be able to address to that types of issues and should also be able to arrange in infrastructure as well as supporting programmes to those types of peoples who have entrepreneurship ideas. The Journal of Nepalese Business Studies Vo. IV, No. 1(2007) pp. 75-82